Call Types of the Oriental Magpie Robin (Copsychus saularis) in Suburban Areas in Kota Samarahan, Sarawak - Manshor, Zahran; Augustine Gawin, Dency Flenny (Borneo Journal of Resource Science and Technology, 2020)
The Oriental Magpie Robin (Copsychus saularis) is among the popular passerines songbird in Borneo. A study on the vocalisation of this tropical species has been conducted at Universiti Malaysia Sarawak (UNIMAS) Campus and Tanjung Bundong village areas, Kota Samarahan, Sarawak starting from March 2015 until February 2017 to understand more on their call types. Call samples were recorded from 38 individuals of Magpie Robin (8 colour-ringed males, 6 colour-ringed females, 10 juveniles and 14 nestlings) during breeding seasons. A total of six call types were successfully identified which were territorial, threat, submissive, juvenile, distress and begging calls. Both territorial and threat calls are uttered in response to the presence of an intruder in the vicinity of nesting sites while begging call is crucial to the nestlings as it stimulates parental food provisioning activities. Distress call was uttered when in stress situations while juvenile calls were associated with learning process to vocalise. Territorial, threat and begging calls were substantially important during breeding season and the survival of Magpie Robins.